Legal Control Over Copyright Protection Using Blockchain Technology - N. Kirsanov, Alexey; A. Popovich, Alexey (International Journal of Criminology and Sociology, 2022)
The development of digital information technologies predetermined the need to develop technical and legal mechanisms of copyright protection. Now the share of copyright in the national economies of most countries is very significant and continues to grow, the main task of national legal systems is to find and implement technical and legal solutions to protect copyright from digital piracy. One of these solutions is block chain technology. The relevance of the research topic rests at the novelty of this technology and the lack of study of issues in the field of theory and law enforcement related to the adaptation and legitimation of relations using block chain technologies, including in the field of copyright protection. The purpose of this article is to analyze the legal qualifications of block chain technology and its application in the field of copyright protection, legitimization of relations associated with the use of block chain technologies in the field of copyright protection. The study revealed that the block chain has features that allow for classification of this technology as a type of technical means of copyright protection, which is the theoretical significance of this study. It has been established that in the field of copyright protection, the block chain performs the function of fixing and confirming the legitimacy of ownership by the author or other right holder of the corresponding work, and provides control over access to the work during authorized use. In the course of the study, the authors assessed the provisions of the current procedural legislation for the use of block chain technologies as evidence in court proceedings for copyright protection and revealed that information from the block chain, including those confirming authorship, can be recognized by the courts as evidence.